2021
DOI: 10.1016/j.ijchp.2021.100225
|View full text |Cite
|
Sign up to set email alerts
|

Student burnout and engagement: Relationship with adolescent use of alcohol and attitudes towards authority

Abstract: Background/Objective The burnout syndrome has been related to development of transgressive attitudes toward norms that facilitate risk behaviors in youth, such as drinking alcohol. On the contrary, academic engagement is related to positive attitudes toward authority which can slow down its use. The objective was analyze the relationships between burnout and academic engagement, attitudes toward authority and use of alcohol. Method : The sample included a total of 1,287 high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 78 publications
1
9
0
5
Order By: Relevance
“…There is a correlation between stress and coping tasks and ongoing burnout and self-efficacy. The results of this study confirm the continued use of selected stress and coping criteria for teacher well-being, and discuss areas for further research and potential use of these indicators [4,5].…”
Section: Introductionsupporting
confidence: 67%
“…There is a correlation between stress and coping tasks and ongoing burnout and self-efficacy. The results of this study confirm the continued use of selected stress and coping criteria for teacher well-being, and discuss areas for further research and potential use of these indicators [4,5].…”
Section: Introductionsupporting
confidence: 67%
“…Por otra parte, Tacca et al (2021), manifiestan que el EA es un elemento esencial para promover aprendizajes, mejores rendimientos y sobre todo bienestar y disfrute de los alumnos en sus estudios. El EA se conforma por tres dimensiones: el vigor, la dedicación y la concentración (Arias et al, 2020;Daura et al, 2020;Pérez et al, 2021;Schaufeli y Bakker, 2004). El Vigor se define como los altos niveles de energía que pone el estudiante para la realización de sus tareas y actividades de estudio (Rigo et al, 2020), también se define como el deseo de esforzarse que tiene el estudiante (Gil y Cruz, 2018).…”
Section: Introductionunclassified
“…Current stage of schooling was positively associated with the age of first alcohol consumption, it meant that the higher the level of schooling at the current stage, the lower the risk of premature alcohol consumption, which may be related to active academic engagement. It had been observed that adolescent students who were actively involved in academics had a high degree of academic dedication [ 71 ]; they immersed themselves in their studies and spent time and energy to improve academic performance, which in turn reduced the occurrence of alcohol use [ 72 ].…”
Section: Discussionmentioning
confidence: 99%